2016
DOI: 10.3897/jhr.49.8066
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography and demography of an Australian native bee Ceratina australensis (Hymenoptera, Apidae) since the last glacial maximum

Abstract: The small carpenter bees, genus Ceratina, are highly diverse, globally distributed, and comprise the sole genus in the tribe Ceratinini. Despite the diversity of the subgenus Neoceratina in the Oriental and IndoMalayan region, Ceratina (Neoceratina) australensis is the only ceratinine species in Australia. We examine the biogeography and demography of C. australensis using haplotype variation at 677 bp of the barcoding region of COI for specimens sampled from four populations within Australia, across Queenslan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
(53 reference statements)
1
15
0
Order By: Relevance
“…Our detection of a significant decrease in genetic diversity in SA corroborates previously determined mitochondrial homogeneity for this population (Dew et al, 2016). Pairwise F ST values are often much higher when calculated using mitochondrial marker data compared with microsatellite data (Carlsson et al, 2004;Goropashnaya et al, 2007) owing to both the high variability of microsatellites and the lower effective population size of mtDNA (Jorde et al, 1998).…”
Section: Discussion Population Genetics and Marker Comparisonssupporting
confidence: 90%
See 4 more Smart Citations
“…Our detection of a significant decrease in genetic diversity in SA corroborates previously determined mitochondrial homogeneity for this population (Dew et al, 2016). Pairwise F ST values are often much higher when calculated using mitochondrial marker data compared with microsatellite data (Carlsson et al, 2004;Goropashnaya et al, 2007) owing to both the high variability of microsatellites and the lower effective population size of mtDNA (Jorde et al, 1998).…”
Section: Discussion Population Genetics and Marker Comparisonssupporting
confidence: 90%
“…A previous assessment of mitochondrial CO1 haplotype variation across the C. australensis range supported an ancestral dispersal out of Asia, coinciding with the last major glaciation event ~18 kya, followed by expansion south and west (Dew et al, 2016). The most southern population sampled during that study was represented by a single haplotype, which indicated either a recent genetic bottleneck or a founding event followed by little to no additional immigration.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations